Penicillin and Cell Wall Synthesis: A Study of Bacillus cereus by Electron Microscopy - Highton, Peter J. (1972)
The changes in wall structure of a penicillinase micro-constitutive strain of Bacillus cereus (569/H/24), on exposure to penicillin, and after its removal by addition of penicillinase, have suggested the following model for the growth of the walls of these cylindrical cells. Longitudinal extension is by addition of material to a large and continuously increasing number of growing points uniformly distributed over the cylindrical surface. Addition is only in the longitudinal direction so that the cell diameter remains constant. Cross walls grow by addition to their inner edge, and on completion the two new rounded ends of the daughter cells are formed by splitting at the outer edge and continued addition at the center. The ends are conserved.